MaxEnt modeling and risk evaluation of chagas disease vectors in the domestic cycle of Hidalgo, Mexico. - Mónica Chico-Avelino; Josefina Ramos-Frías; Adriana López-Mejía; Santiago Martínez-Calvillo; Rebeca Georgina Manning-Cela (PLoS Neglected Tropical Diseases)
This study developed MaxEnt models to determine the potential distribution of four triatomine vector species of Chagas disease in the domestic cycle in Hidalgo state, Mexico: Triatoma dimidiata (Latreille, 1811), T. mexicana (Herrich-Schaeffeer, 1848), T. gerstaeckeri (Stål, 1859), and T. barberi (Usinger, 1939). We analyzed over 500 occurrence records alongside selected bioclimatic, topographic, and land cover variables. Key determinants influencing each species' distribution included climate types, altitude, and anthropogenic factors. Model validation used statistical methods with Area Under the Curve (AUC) metrics, where AUCs ≥ 0.8 indicated good performance, along with experimental validation performed for the first time in the context of Chagas disease through targeted field collections at predicted sites. The results showed high concordance between model classifications and field data, confirming the models' validity. The identified suitable habitat areas correlated with known ranges of the vector species, providing insights into Chagas disease transmission risk in the domestic cycle. This integrated approach not only validated the presence and absence of the modeled species but also documented the current presence of three vector species, enhancing our understanding of factors influencing vector distributions. Ultimately, this research aims to inform epidemiological control efforts and improve Chagas disease surveillance strategies.